2015
DOI: 10.1515/fsmu-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Annual growth trends and response to weather of larch trees at Järvselja Training and Experimental Forest Center stands (Estonia)

Abstract: Larch is widely used in tree-ring studies, while tree-ring width and signature years provide information on environmental changes with annual resolution. The aim of the study was to build tree-ring (TR), early- (EW) and latewood (LW) width chronologies by larch species (Hybrid, European, Russian, Japanese, Kuril), and to study the response of the radial increment of larches to weather at Järvselja forest stands by using correlation, redundancy analysis, and the pointer year method. The increment cores were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Study area 3 in south Belarus was exceptional, since it was the only case when the correlation was positive for all PDSI diff variables. However, the number of sampled trees there (16) was the lowest of all the study areas ( Table 1).…”
Section: Climatic Variability and Growth Releasementioning
confidence: 98%
See 1 more Smart Citation
“…Study area 3 in south Belarus was exceptional, since it was the only case when the correlation was positive for all PDSI diff variables. However, the number of sampled trees there (16) was the lowest of all the study areas ( Table 1).…”
Section: Climatic Variability and Growth Releasementioning
confidence: 98%
“…Tree-ring data are useful for exploring the effects of soil moisture status and several other factors on tree and forest growth. High-frequency signals extracted from tree-ring series can be utilized to address relationships with short-term climatic variability, and a number of studies have identified links between temperature and precipitation on tree radial growth at an annual scale using ring-width data of various tree species in Estonia [14][15][16][17][18] and other countries in the Baltic region [19][20][21][22]. Low-frequency signals contained in ring-width series can be associated with tree size or age and various endogenous and exogenous disturbances [23].…”
Section: Introductionmentioning
confidence: 99%